2018
DOI: 10.1016/j.jconrel.2018.10.026
|View full text |Cite
|
Sign up to set email alerts
|

A novel elastin-like polypeptide drug carrier for cyclosporine A improves tear flow in a mouse model of Sjögren's syndrome

Abstract: As a potent macrolide immunosuppressant, cyclosporine A (CsA) is used to treat multiple autoimmune diseases, including non-autoimmune and autoimmune-mediated dry eye disease, rheumatoid arthritis and psoriasis. Despite its potency, CsA has poor solubility, poor bioavailability, and can cause serious adverse reactions such as nephrotoxicity and neurotoxicity. To overcome these limitations, we invented a new strategy to carry CsA by fusing its cognate human receptor, cyclophilin A (CypA), to a 73 kDa elastin-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 63 publications
2
14
0
Order By: Relevance
“…In this research, we performed database analysis, in vitro and animal assays and found the potential link between CYPA expression and SOC progression. CYPA expression, similar to previous studies, was obviously correlated with clinical features of SOC patients, including tumor stage and lymphnode metastasis [33][34][35][36][37][38]. Our results are similar with previous studies indicating the important role of CYPA in tumorigenesis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this research, we performed database analysis, in vitro and animal assays and found the potential link between CYPA expression and SOC progression. CYPA expression, similar to previous studies, was obviously correlated with clinical features of SOC patients, including tumor stage and lymphnode metastasis [33][34][35][36][37][38]. Our results are similar with previous studies indicating the important role of CYPA in tumorigenesis.…”
Section: Discussionsupporting
confidence: 91%
“…CYPA was first found as the target of cyclosporin A (CsA), an immunosuppressive drug, which has been used for the treatment of several tumors, including ovarian cancer [37]. Although the regulatory mechanism underlying CYPA promoting OC progression is still unclear, previous studies showed that CSA could bind to CYPA and thus increase the effects of chemotherapy [38].…”
Section: Discussionmentioning
confidence: 99%
“…The clearance of the fusion protein was determined to be 0.28 mL/hr, which is consistent with other reported clearance of high molecular weight ELPs. 13,14 The volume of distribution was calculated to be 1.92 mL, which is consistent with the expected volume of blood in these mice. Bioluminescence images of spleen, kidneys, and liver showed that α-CD99-A192 nanoworms still resided in those organs 96 hours post-injection and accumulated at a higher level in the liver as compared to the spleen and kidney (p ≤0.05) (Representative bioluminescence images and quantification Fig.…”
Section: Pk Profile Of α-Cd99-a192 Nanoworms Fits the Biexponential Decay Modelsupporting
confidence: 72%
“…Despite being a very popular line of treatment for patients with DED, optimal doses and the optimal duration of treatment are still debatable. Furthermore, adverse effects such as foreign body sensation, conjunctival hyperemia, and epiphora can accompany treatment with this medicine [ 46 , 47 , 48 ]. Another alternative could be lifitegrast.…”
Section: Ocular Pathologies Related To Oxidative Stress and Inflammentioning
confidence: 99%